Técnica de Kaltenborn para el mejoramiento de la movilidad articular del adulto mayor con gonartrosis, 2018 - Merino Lara, Priscila Gabriela (2019)
The present research considers that the technique Kaltenborn is as an alternative for increasing joint mobility and decreasing pain in patients with osteoarthritis. The purpose was to analyze the information about the effectiveness of Kaltenborn technique for improvement joint mobility of older adults with knee osteoarthritis. The level of satisfactory of this research was descriptive. To collect the information about the subject, it was made by searching indexed magazines in English and Spanish, and academic repositories. The inclusion criteria’s were, the dates of publication less than 5 years, the scale score more than 6 points PEDro. The population studied in the largest number of items corresponded to the age group of 61 to 80 years old. The number of participants in the gathered research varies from 15 to 30 people. The bearing line is used for the evaluation of joint ranges. At the end of the literature review, the results demonstrate the use of technical Kaltenborn, has been efficient in all the studies reviewed. However, their effectiveness varies according to the joint member in which the technique was applied, as well as the duration of the treatment.